Release of cetyl pyridinium chloride from fatty acid chelate temporary dental cement - Andrew Hurt; Nichola J. Coleman; Tamer Tüzüner; Bora Bagis; Fatih Mehmet Korkmaz; John W. Nicholson (Acta Biomaterialia Odontologica Scandinavica)
Objective To determine whether the antimicrobial nature of a fatty acid chelate temporary dental cement can be enhanced by the addition of 5% cetyl pyridinium chloride (CPC). Materials and methods The temporary cement, Cavex Temporary was employed, and additions of CPC were made to either the base or the catalyst paste prior to mixing the cement. Release of CPC from set cement specimens was followed using reverse-phase HPLC for a period of up to 2 weeks following specimen preparation. Potential interactions between Cavex and CPC were examined by Fourier transform infrared spectroscopy (FTIR) and antimicrobial effects were determined using zone of inhibition measurements after 24 h with disc-shaped specimens in cultured Streptococcus mutans. Results FTIR showed no interaction between CPC and the components of the cement. CPC release was found to follow a diffusion mechanism for the first 6 h or so, and to equilibrate after approximately 2 weeks, with no significant differences between release profiles when the additive was incorporated into the base or the catalyst paste. Diffusion was rapid, and had a diffusion coefficient of approximately 1 × 10−9 m2 s−1 in both cases. Total release was in the range 10–12% of the CPC loading. Zones of inhibition around discs containing CPC were significantly larger than those around the control discs of CPC-free cement. Conclusions The antimicrobial character of this temporary cement can be enhanced by the addition of CPC. Such enhancement is of potential clinical value, though further in vivo work is needed to confirm this.